Buying And Selling Transactions On Social Media Are Prohibited: Review Of The Law Of Buying And Selling Between Justice, Welfare And Human Rights - Riduwansah Riduwansah; Iwan Ridwan Paturochman; Zulqarnain Zulqarnain; Muktar Muktar; Indriya Fathmi (Utan Kayu Publishing, 2024)
Technology has greatly influenced commercial activity, particularly in the area of electronic commerce, where products or services can be promoted, marketed, sold and purchased electronically. While this has brought many benefits, it has also raised concerns regarding violating Consumer Rights. Law No. 8 Year 1999 aims to ensure legal certainty in e-commerce transactions. This article discusses the regulation of the legal protection of consumers in e-commerce transactions and the problems that it is facing. The research method is based on a normative legal approach. Written law and literature are examined and related to real events. The analysis conducted is descriptive, collecting data and relating it to real events. It is concluded that consumer protection regulations have not been effective in preventing fraud committed by economic actors in electronic transactions. In order to prevent crimes committed by economic actors and to provide a legal umbrella for consumers, the existence of a consumer protection law is expected.